Lewis Acid-Promoted Diastereoselective Cross-Coupling of Boronic Acids and Aryl-Substituted 1,2-Diols - 유희선 (The Graduate School, Ajou University, 2021)
A Lewis acid-promoted highly diastereoselective C(sp3)–C(sp2) cross-coupling reaction of aryl-substituted 1,2-diols and a variety of styryl, aryl, heteroaryl and polyaryl boronic acids as nucleophiles has been developed in a one-pot process under mild reaction conditions. The regioselective opening of aryl-substituted cyclic boronic esters promoted by a Brønsted or Lewis acid and subsequent intramolecular 1,4-transfer of the carbon ligand from boron atom to the same face of the resulting resonance-stabilized planar benzylic carbenium ion in a stereospecific fashion led to highly diastereoselective C–C bond formation at the benzylic carbon center. The synthetic value of this method has been demonstrated by a unified enantioselective total synthesis of 9-norneolignan natural products (–)-agatharesinol, (–)-agatharesinol acetonide, (–)-sugiresinol and (+)-hinokiresinol in 6 to 8 steps from the commercially available methyl 3-(4-hydroxyphenyl)acrylate.
학위논문(박사)--아주대학교 일반대학원 :약학과,2021. 8
Keywords: 9-norneolignan; boronic acid; cross coupling; diol; lewis acid